Translation, reliability and validity of the Turkish version of Scoliosis Japanese Questionnaire-27 in adolescent idiopathic scoliosis - KURU ÇOLAK, TUĞBA (My University, 2023)
Purpose: Disease-specific scales which evaluate QoL are needed to evaluate treatment outcomes, and to compare the effects of different treatments. The outcome measures evaluating quality of life in adolescent idiopathic scoliosis are limited. The purpose of this study was to examine the validity and reliability of the Turkish version of the Scoliosis Japanese Questionnaire-27 (SJ-27) in adolescent idiopathic scoliosis. Methods: The SJ-27 questionnaire was translated into Turkish and 61 female patients filled out the translated version (TRv.SJ-27) twice to measure the test–retest reliability of the scale. Internal reliability of the questionnaire was estimated using Cronbach’s α coefficient. The intraclass correlation coefficient was analysed for each item. Discriminant validity and convergent validity were determined by correlations with Cobb angle, ATR and the SRS-22r scale. Results: The mean Cobb angle was 25.8° and the ATR angle was 8.8°. Cronbach’s α value was estimated as 0.935. The test–retest correlation coefficient for the item-total score was 0.877 (p = 0.000). Validity analysis showed a significantly positive correlation between the TRv.SJ-27 total score and Cobb and ATR angles, and a significantly negative relationship was found between the TRv.SJ-27 and SRS-22r scores. Conclusions: It would be useful to use different outcome measures to assess the scoliosis-specific quality of life in clinical practice and research. The findings suggest that the Turkish version of Scoliosis Japanese Questionnaire-27 is a valid and reliable measure to assess Turkish patients with AIS.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; ORTHOPEDICS; Ortopedi ve Spor Hekimliği; Orthopedics and Sports Medicine; Quality of life; Reliability; Scoliosis; Spine